High-Frequency Litz "Air-Gap" Windings for High-Power Density Electrical Machines. Issue 7 (21st April 2017) - Martin, Jonathan; Yoon, Andy; Jin, Austin; Haran, Kiruba S.
ABSTRACT: This paper describes the development of high-frequency air-gap windings for a 1 MW, 96% efficient permanent magnet (PM) motor, targeted at 13 kW/kg. Due to the power level and high-specific power requirements, special attention has to be paid to the electromagnetic, thermal, and mechanical performance for the high-frequency coils. Specifically, AC losses have to be minimized while fill factor and thermal conductivity of the assembly are maximized. The paper presents analytical and finite element-based AC loss studies along with experimental validation by indirect balanced calorimetry, and shares the results which should be scalable for other large machines. Hardware development and corresponding manufacturing process are also described.